Thermoelectric Power System From A Liquid-Fueled Combustor - Razali, Muhammad Safuan (Universiti Sains Malaysia, 2018)
The aim of this project is to design a combustor to generate electricity from the thermoelectric (TE) cells. The combustion and performance characteristics of the combustor for TE power generation is also evaluated. The experimental work involved the direct generation of heat from the combustion of liquid fuel to generate electricity via the thermoelectric cells. The operating range of the combustor was varied to cover from the fuel-lean to the fuel-rich region. The electricity generated was measured using a multimeter. It was found that power generated is directly proportional to the current (as in data for n = 1, P = 0.00975 W and I = 0.010 A, n = 2, P = 0.01182 W and I = 0.012 A, n = 3, P = 0.02140 W and I = 0.020 A) and power is also directly proportional to the voltage (as in data for n = 1, P = 0.00975 W and V = 0.975 V, n = 2, P = 0.01182 W and V = 0.985 V, n = 3, P = 0.02140 W and V = 1.078 V). In conclusion, the performance and combustion characteristics of thermoelectric power generated by combustor were evaluated in this experiment. The combustor was successfully designed.